Enhanced Pyroelectric Coefficient in Ferroelectric Lead Zirconium Titanate Thick Films for Thermal Energy Harvesting Applications. (1st February 2022) - Vandana,; Gupta, Reema; Tandon, R. P.; Tomar, Monika
Abstract : Due to increase in growth population and energy demand, energy harvesting technology has become a sensational topic of research community. Amongst all the available energy harvesting technologies (mechanical, magnetic, wind, hydrothermal), harvesting waste heat has gained a lot of interest because of its cost effectiveness and availability of significant thermal fluctuations in industrial processes as well as in nearby surroundings. Therefore, efforts have been made on harvesting thermal energy through pyroelectric devices. Such devices have huge range of applications in fire alarms, heat sensors, infrared detectors, thermal imaging, gas analysis and so on. In the present study, the pyroelectric Lead Zirconium Titanate (PZT) thick films grown using modified sol-gel approach have been used for pyroelectric energy conversion. The effect of annealing temperature (450 °C, 450 °C and 650 °C) on the growth of PZT films has been monitored by investigating their dielectric, ferroelectric and pyroelectric properties. An appreciable enhancement in saturation and remnant polarizations from 17 μ C cm −2 to 24 μ C cm −2 P s and 13 μ C cm −2 to 2 2 μ C cm −2 P r has been obtained when annealed temperature is increased from 550 °C to 650 °C respectively. A visible change in dielectric constant is also observed from 207 to 325 from dielectric constant–frequency curves with very small change in dielectric losses from 0.06 to 0.10 with increase in the annealing temperature from 550 °C to 650 °C at 1 MHz. The pyro electric coefficient and figure of merit are found to increase from 25 × 10 −3 Cm −2 K −1 to 230 × 10 −3 Cm −2 K −1 (p) and from 2.2 m 2 C −1 to 20 m 2 C −1 for the optimized PZT thick film based pyroelectric device with increase in the external DC bias field from 0.5 V to 2.5 V. The enhanced results of pyroelectric coefficient and figure of merit achieved in the present work are good indication of electrical energy harvesting through pyroelectricity.